تفسیر ’’ تبصرہ‘‘ از سید ریاض حسین شاہ کا منہج و اسلوب اور خصائص : تحقیقی و تجزیاتی جائزہ: A Scholarly and Critical Analysis of the Methodological Framework, Literary Style, and Unique Attributes of Tafseer Tabsarah by Syed Riaz Hussain Shah - Muhammad Siddique; Fraz Ahmed (International Research Journal of Arabic and Islamic Studies, 2024)
This study examines the various methodologies employed by Urdu commentators in their interpretations of the Quran. The author primarily relies on the works of established commentators such as Abdullah ibn Abbas, Ibn Kathir, Imam Tabari, Fakhr al-Din al-Razi, Ibn Arabi, al-Qurtubi, and al-Alusi, among others. The core principle of this interpretation is to regard the Quran as the primary source, with the Hadith serving as a secondary resource, a method referred to as "Tafsir bil-Ma'thoor." The author incorporates the opinions of earlier scholars alongside Quranic verses and Hadith, ensuring a comprehensive understanding of the text. The study considers linguistic aspects, historical contexts, and educational dimensions, facilitating clarity in meaning for readers. Additionally, the use of poetry enhances the appeal of the interpretation, and the referencing system is clearly outlined. The simplicity and brevity of the language make it accessible to a general audience, and differing opinions on contentious issues are presented thoughtfully to avoid fostering discord. However, a notable shortcoming is the occasional omission of original phrases, which can hinder the full comprehension of certain meanings.